AUTOMATION OF LABORATORY TESTING: ADVANTAGES AND CHALLENGES IN EVERYDAY PRACTICE - Abdunabiyeva Aziza Ulug’bek qizi; Isomadinova Lola Kamolidinovna; Karimova Linara Alixanovna; Abduqodirova Dilnura (Web of Journals Publishing, 2025)
Automation of laboratory testing has become a key area of development in modern medicine. This article analyzes the main advantages of automation, such as increased accuracy, reduced time consumption, and minimization of human error. It also discusses the challenges associated with implementing automated systems, including staff training, high initial costs, and standardization issues.
Keywords: Automation, laboratory testing, accuracy, standardization, medical technology.